The Impact of Foreign Aid on Infrastructure Development in Lao PDR. - Her, Pheng; Liang, Shuanglu (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This paper analyzes the impact of foreign aid on infrastructure development. Panel data from 17 provinces in Laos from 2008 to 2019 were used and implied with the Pooled OLS, fixed effects and random effects models. The Hausman test showed that a p-value less than 0.05 indicates that the panel regression model should use a fixed-effects model instead of a random-effects model. As a fixed effects model to examine the impact of foreign aid on infrastructure development. It shows that foreign aid has a positive effect, or in other words, foreign aid helps to improve infrastructure in Laos, such as roads, electrification, telecommunications and airports, but its impact is very small. Assuming that other factors remain constant, a one unit increase in foreign aid leads to a 0.052-unit improvement in infrastructure. The heterogeneity analysis of the impact of infrastructure accumulation of different donors in Laos shows that only the large donor countries have a significant impact. Article history: Accepted 10 April 2025 Revised 12 June 2025 Accepted 16 June 2025 SIMILARITY INDEX = 0.00 %